System management of a wind-energy converter. - Kana, C.L.
Wind energy converters are commonly used in converting wind energy into useful mechanical and electrical energies. But the problems of smooth start, tower effect and oscillations caused by aerodynamic forces acting on the rotor cause fluctuations in its power output. A system management was designed to reduce these effects. It consists of a microcontroller. This was verified with the help of laboratory test bench model of a wind energy converter driving an asynchronous generator. The model was a direct replication of a real wind energy converter and was designed with the help of a wind rotor simulator program. The aerodynamic data for the test were obtained from the rotor blade profile of real equipment (Ventis 100). The microcontroller was programmed with a selected power control method. The test showed that the system management compensates the power fluctuations and enables the smooth start of the wind energy converter. Furthermore, it quickly shuts off the wind energy converter in stormy and calm periods
Keywords: Ventis 100 wind turbine; Aerodynamic forces; Asynchronous generator; Microcontroller; Oscillations; Power control method; Power fluctuations compensation; Power output fluctuations; Rotor blade profile; Smooth start; System management; Tower effect; Wind rotor simulator program; Wind-energy converter